Understanding Strategic Reactiveness Influences on Entrepreneurial Management Tendencie - Abdul Majid, Izaidin; Ismail, Kamariah; Md. Saad, Mohd Shamsuri (2011)
This study explores the relationship between strategic reactiveness (SR) and Entrepreneurial Management (EM) tendencies of SMEs sector within the states of Melaka and Johor in Malaysia. This research considers that strategy-related variables are competitively aggressive and adaptive. Strategic planning allows organizations to anticipate changes and create strategic options for those changes. It is commonly perceived that SR will have a positive relationship with EM. Respondents for this research include CEOs, owner-managers and entrepreneurs. Data was collected by distributing questionnaire to 200 small and medium-sized enterprises selected randomly from both the services and manufacturing sectors. This paper will explore and explain the concept and variables related to the research as well as brief demographic descriptions of the respondents.